Recent Advances of Pullulan and/or Dextran-Based Materials for Bone Tissue Engineering Strategies in Preclinical Studies: A Systematic Review - Ahmed Omar, Naïma; Amédée, Joëlle; Letourneur, Didier; Fricain, Jean-Christophe; Fenelon, Mathilde (Frontiers in Bioengineering and Biotechnology, 2022)
Bone tissue engineering (BTE) strategies are increasingly investigated to overcome the limitations of currently used bone substitutes and to improve the bone regeneration process. Among the natural polymers used for tissue engineering, dextran and pullulan appear as natural hydrophilic polysaccharides that became promising biomaterials for BTE. This systematic review aimed to present the different published applications of pullulan and dextran-based biomaterials for BTE. An electronic search in Pubmed, Scopus, and Web of Science databases was conducted. Selection of articles was performed following PRISMA guidelines. This systematic review led to the inclusion of 28 articles on the use of pullulan and/or dextran-based biomaterials to promote bone regeneration in preclinical models. Sixteen studies focused on dextran-based materials for bone regeneration, six on pullulan substitutes and six on the combination of pullulan and dextran. Several strategies have been developed to provide bone regeneration capacity, mainly through their fabrication processes (functionalization methods, cross-linking process), or the addition of bioactive elements. We have summarized here the strategies employed to use the polysaccharide scaffolds (fabrication process, composition, application usages, route of administration), and we highlighted their relevance and limitations for BTE applications.